AGRICULTURAL AND TOURISTIC POTENTIAL OF THE NORTHEASTERN DEVELOPMENT REGION-ROMANIA - Stejărel, Brezuleanu; Carmen-Olguţa, Brezuleanu; George, Ungureanu; Adrian, Ungureanu (Economics of Agriculture, 2018)
The process of diversifcation and integration of several economic branches determines major changes in the economic structure of the individual farms and in the life of the rural population. Among the great variety of activities present in the rural environment, an important part with a tendency of expansion is represented by agrotourist activity. This paper analyzes turistcal potential in the part of North-Eastern Development Region-Romania